The Use of Think Pair and Share (TPS) Technique to Improve Students’ Reading Ability at SMA N 11 Wetang MBD - Rumurlely, Martina; Nikijuluw, Renata C. G. V.; Meyer, Fredi (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2024)
Think Pair And Share (TPS) is an effective technique in teaching reading in-class activity. The purpose of this research is to (1)How can the Think-Pair-Share technique improve students' reading skills in the first grade of SMA NEG 11 WETANG MBD? (2) What are students' responses about the Think-Pair-Share technique in reading skills at the first grade of SMA NEG 11 WETANG MBD? This classroom action research (CAR) was conducted in two cycles. Each cycle consists of planning, acting, observing and reflecting. The data for this research was the students' reading skills. The researcher used a test, Questioner and Observation, to collect the data. This research was done with an SMA Negeri 11 Wetang MBD English teacher. Based on the result and the discussion, it concluded that applying the Think-Pair-Share technique improved students' reading skills in the first grade of SMA NEG 11 WETANG MBD. The students were actively and enthusiastically involved in the teaching-learning process. It made it easier for the students to understand the material, so it could improve the student's reading comprehension ability. This could be seen from the result obtained of action on cycle I 60, where 00% of students reached KKM. Then, performance in cycle II increased to 90.00% of students who reached KKM.